The Use of Technology to Promote English Learning - Parra, Miguel (CIEX JOURNAL, 2023)
The use of technology in the language teaching and learning field has become a key component of the learning process, both inside and outside the classroom. The rapid evolution of technologies shows us the importance of being aligned with them in order to be updated and be involved in the effective digital tools that technology offers us, where in most cases, technology is used in every language class. Furthermore, teachers can implement classroom activities using technology as a complementary tool, which improves language learning. This research focuses on how using new technologies through teaching activities can help students learn English as a foreign language.